Divergent pattern of functional connectivity within the dorsal attention network differentiates schizophrenia and bipolar disorder patients - Chrobak, Adrian Andrzej; Bielak, Sylwia; Nowaczek, Dominik; Żyrkowska, Aleksandra; Sobczak, Anna Maria; Fafrowicz, Magdalena; Bryll, Amira; Marek, Tadeusz; Dudek, Dominika; Siwek, Marcin (Frontiers in Psychiatry, 2024)
Introduction: Schizophrenia (SZ) and bipolar disorder (BD) share common clinical features, symptoms and neurocognitive deficits, what results in common misdiagnosis. Recently it has been suggested that alterations within brain networks associated with perceptual organization yield potential to distinguish SZ and BD individuals. The aim of our study was to evaluate whether functional connectivity (FC) of the dorsal attention network (DAN) may differentiate both conditions.Methods: The study involved 90 participants: 30 remitted SZ patients, 30 euthymic BD patients and 30 healthy controls (HC). Resting state functional magnetic resonance imaging was used to compare the groups in terms of the FC within the core nodes of the DAN, involving frontal eye fields (FEF) and intraparietal sulcus (IPS) Results: BD patients presented weaker inter-hemispheric FC between right and left FEF than HC. While SZ did not differ from HC in terms of inter-FEF connectivity, they have presented increased inter-and intra-hemispheric FC between FEF and IPS. When compared with BD, SZ patients showed increased FC between right FEF and other nodes of the network (bilateral IPS and left FEF) Conclusion: We have shown that altered resting state FC within DAN differentiates BD, SZ and HC groups. Divergent pattern of FC within DAN consisting of hypoconnectivity in BD and hyperconnectivity in SZ, might yield a candidate biomarker for differential diagnosis between both conditions. More highly powered studies are needed to confirm these possibilities.